Rethinking construction: inclusion of slow learners as taker-off in quantity surveying practice - Masidah, Abdul Majid; Nurul Izatti, M. Ashaari; Suhaida @ Suhana, Kamarudin; Nurul Aini, Osman; Mohamad Saifulnizam, Mohd Suhaimi (2017)
The objective of this paper is to present the preliminary findings regarding the participation of OKU with learning disability in Science Technology, Engineering and Mathematics (STEM) sectors. Review of the works of past researchers suggested that OKU is a potential workforce in STEM sectors but still under-represented due to lack of efforts from stakeholders and learning institutions in providing information on the opportunities that are available. A research has been initiated to explore the potential of slow learners to become workforce in the construction industry as a taker off – part of work of a Quantity Surveyor. Against the findings from the literature review, the modest attempt to attract slow learners to become taker off in the construction industry require the formulation of appropriate learning environment and strong support from the respective key players and stakeholders